Four cases of solitary fibrous tumour of the eye and orbit: one with sarcomatous transformation after radiotherapy and one in a 5-year-old child's eyelid. Issue 3 (9th October 2013) - Blandamura, Stella; Alaggio, Rita; Bettini, Giordana; Guzzardo, Vincenza; Valentini, Elisa; Bedogni, Alberto
Abstract : Background: Solitary fibrous tumour (SFT) is quite a rare neoplasm involving the eye and the orbit. It is described as showing benign behaviour in adults, but malignant cases are exceptionally reported in this location. This report describes four new cases of SFT/giant cell angiofibroma (GCA) of the eyelid and orbit, one in a 5-year-old child, and one with sarcomatous dedifferentiated transformation occurring 9 years after radiotherapy. Methods: Four cases of ocular SFT/GCA were retrieved from the database of the Pathological Anatomy Unit, University of Padova; immunohistochemistry and RT-PCR were used to identify COL1A1—PDBGF fusion gene transcripts in all cases. Results: In case 1, late relapse 9 years later was characterised by abrupt transition into a high-grade component, associated with a non-distinctive high-grade sarcomatous area. The latter component was CD34, CD99 and Bcl2 negative and smooth muscle actin positive. Molecular characterisation showed the absence of COL1A1-PDGFB fusion transcripts in cases 1, 3 and 4, excluded diagnosis of giant cell fibroblastoma in all cases. Analysis could not be performed in case 2. Conclusions: An eyelid SFT/GCA in a 5-year-old child is the youngest case reported in the literature, indicating that the tumour is not exclusive to adults. The case with sarcomatous transformation, with dedifferentiated features occurring 9 years after radiotherapy, raises some questions about the choice of treatment for ocular SFT, in which excision is sometimes difficult without devastating surgery.